PENINGKATAN POTENSI DESA CIGUGURGIRANG MELALUI PELATIHAN PENGOLAHAN BAHAN MAKANAN BERBAHAN DASAR HASIL BUMI PERTANIAN DAN PETERNAKAN - Rochiyat Setiawan (LPPM and Travel Operation Department Universitas Asa Indonesia, 2022)
Cigugurgirang Village is a village located in Parongpong District, West Bandung Regency, Cigugurgirang Village has a lot of agricultural products that can have an impact on the economy of the local community because this village has enormous potential, especially in agro-tourism that produces vegetables and fruits and livestock, but the community in this village lack of creativity for the produce into processed food which can also have a large enough impact for business actors such as Micro, Small and Medium Enterprises (MSMEs), from the results of the research are observations and structured interviews in Cigugurgirang Village that the community needs to be trained to encourage skills and knowledge for the community and business actors by using SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) such as increasing food innovation made from natural products such as broccoli which is a product of largest land and livestock products. The results of the processing using a swot analysis matrix turned out to be in the Strength and Opportunity (S-O) strategy that it was necessary to empower human resources and involve village development with academics and local government.